2021
DOI: 10.1177/23259671211002282
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary Lateral Extra-articular Tenodesis for Residual Anterolateral Rotatory Instability in Patients Undergoing Single-Bundle Anterior Cruciate Ligament Reconstruction: A Meta-analysis of Randomized Controlled Trials

Abstract: Background: The combination of lateral extra-articular tenodesis (LET) with primary single-bundle anterior cruciate ligament (ACL) reconstruction (ACLR) remains controversial. Purpose: To determine whether the combination of LET with single-bundle ACLR provides greater control of anterolateral rotatory instability and improved clinical outcomes compared with ACLR alone. Study Design: Systematic review; Level of evidence, 2. Methods: PubMed, Embase, and the Cochrane Central Register of Controlled Trials databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 53 publications
(136 reference statements)
1
7
0
Order By: Relevance
“…It demonstrated that concomitant LET results in a 3-fold lower risk of graft failure. 33 The second relevant finding of the present study is that combining LET with ACL reconstruction significantly improved both anteroposterior and rotatory knee stability in this skeletally immature cohort without increasing the risk of complications. This is in accordance with biomechanical evidence that demonstrates that LET in combination with ACL reconstruction significantly reduces both anterior tibial translation and tibial internal rotation as compared with isolated ACL reconstructions.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…It demonstrated that concomitant LET results in a 3-fold lower risk of graft failure. 33 The second relevant finding of the present study is that combining LET with ACL reconstruction significantly improved both anteroposterior and rotatory knee stability in this skeletally immature cohort without increasing the risk of complications. This is in accordance with biomechanical evidence that demonstrates that LET in combination with ACL reconstruction significantly reduces both anterior tibial translation and tibial internal rotation as compared with isolated ACL reconstructions.…”
Section: Discussionsupporting
confidence: 50%
“…2,17,44 Recently, combining a lateral extra-articular tenodesis (LET) with ACL reconstruction has been reported to significantly decrease failure rates while improving objective rotatory stability and the postoperative activity level. 33 As a result, LET has been strongly recommended for patients at high risk of graft failure. Indications include patients \25 years of age, patients practicing pivoting sports, patients with joint hyperlaxity, and patients with a high-grade preoperative instability.…”
mentioning
confidence: 99%
“…The most important findings of this retrospective case series of 117 ACL-injured knees were: (1) ALC injury, visualized as hemorrhage of the anterolateral capsule during diagnostic arthroscopy, was observed in 19% of ACL-injured knees, an injury incidence significantly less than that observed on MRI (53%) or ultrasound (63%); (2) ALC injury incidence and severity did not significantly differ between MRI and US grading scales; (3) No ALC injury grading scale on any imaging modality meaningfully correlated with physical examination maneuvers for anterolateral knee stability, including Lachman, anterior drawer, and pivot shift tests.…”
Section: Discussionmentioning
confidence: 77%
“…The anterolateral complex (ALC) of the knee, comprised of several structures including the anterolateral capsule and its variable thickening, most recently referred to as the anterolateral ligament (ALL), is a secondary stabilizer to the ACL in controlling anterolateral rotatory stability of the knee. [1] Surgical augmentation of the ALC combined with anatomic ACLR has been reported to improve anterolateral rotary knee stability and reduce graft failure as compared to anatomic ALCR alone at short-term follow-up in a young and active patient population [2][3][4][5] but the long-term outcomes and indications for ALC augmentation remain unclear. [1] Limiting efforts to define surgical indications for ALC augmentation is the variability in the reported incidence of concomitant ALC injury.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 1,010 patients from six randomized controlled trials by Mao et al 114 illustrated a lower risk of graft failure in those who had ACLR and LET compared to those who had isolated ACLR. Of significance is the STABILITY study by Getgood et al 117 This is the largest randomized multicenter study to date, looking at ACLR clinical failure between two ACLR groups – single-bundle hamstring tendon autograft without LET and with LET – in individuals between 14–25 years old.…”
Section: Lateral Extra-articular Proceduresmentioning
confidence: 99%